UJI KEMAMPUAN PRODUKSI SITOKININ OLEH RHIZOBAKTERI - Tri Wijiastuti; Agung Suprihadi; Baedah Rupaedah (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2013)
Plant growth regulators have a role in the process of growth and development of a plant. One of the Plant growth regulators which play an important role in process of growth and development is cytokinin. Cytokinin are able to stimulate division and cell enlargement, accelerate formation of organs, delay aging of various types of plants, and increase number and size of leaves. The utilization of rhizobacteria which is capable in producing cytokinin as a basic component of biological fertilizer has a very important role in improving the growth of plants. This research aims to select the capability of rhizobacteria isolates which are able to produce cytokinin and determine morphological characteristics and biochemical characteristics of potential rhizobacteria isolates as a cytokinin producer. The research was conducted at the Laboratory Agromikrobiologi, Biotechnology Research Center, Agency for the Assessment and Application of Technology, Puspitek, Serpong. The research procedure was rhizobacteria cultivation and extraction of cytokinin from rhizobacteria culture, then detect cytokinin using the method of thin layer chromatography (TLC) and high performance liquid chromatography (HPLC). The results showed that the isolates which were capable to producing cytokinin was Jember 2.2 with a concentration of 92 mg L-1 and expected as Pseudomonas genus bacteria. Keywords : biofertilizers, rhizobacteria, cytokinin.